Assessing the impact of salinity stress on some morpho-physiological traits of two chickpea genotypes under hydroponic conditions - Sobh, Mawia; Basal, Oqba; Al-Ouda, Ayman Shehada; Veres, Szilvia (Acta Agraria Debreceniensis, 2024)
Evaluating the performance of crop species to salinity stress is considered an intricate task due to differences in performance, response and susceptibility at different phenological stages of chickpea crop. Assessment of the performance of chickpea genotypes in response to NaCl-induced salinity stress at the initial vegetative phase is of great importance to have a crystal idea about the threshold level of tolerance. An experiment was carried out under hydroponic conditions to evaluate the performance of two chickpea genotypes (ELMO and ORION), in response to different salinity levels (0, 25, 50 and 75 mM NaCl) as factorial arrangement under completely randomized design with three replications. The average of shoot and root dry matter weight was significantly higher for the ELMO genotype at the control treatment (1.143, 0.4133 g respectively), while it was significantly lower in the two genotypes ORION and ELMO at the highest salinity level (0.267 and 0.2700; 0.0433 and 0.0533 g respectively). The root to shoot ratio was significantly higher in both genotypes in the control and the lowest salt level (25 mM NaCl), without significant differences among them (47.98, 43.30, 37.10 and 36.25% respectively). The relative water content and stomatal conductance were significantly higher in the ORION genotype (88.01%; 335.40 mmol m-2 s-1) compared to ELMO (84.09%; 299.10 mmol m-2 s-1), and increasing salinity level caused a proportional decline in both traits, where they were significantly lower at the highest salt level (75Mm) (77.45%; 87.50 mmol m-2 s-1). Results indicate genotypic variability in response to NaCl-induced salinity stress under hydroponic conditions and the physiological traits are more expressive and reliable as selection criteria than morphological ones.